Conversor CC-CC ZVZCS de três níveis com ampla faixa de comutação suave - Geraldis, José Luiz Saviel (2022)
This work presents the analysis of a topology of the DC-DC three-level half bridge converter operating with ZVS in the active switches and ZCS in the output rectifier diodes, called HB-TL-ZVZCS-PWM (Half Bridge Converter Three-Level with Zero Voltage and Zero Current with Pulse Width Modulation). The circuit allows reducing the voltage stress on its active switches, thus being suitable for applications with higher input voltage levels. In addition, the use of an auxiliary inductance contributes to widening the soft-switching range. The static and dynamic analyses are performed, providing the basis for the development of a step-by-step design methodology as well as for proposing a control system for proper closed-loop operation. Experimental results obtained from tests with a 1 kW prototype, operating with a switching frequency of 100 kHz, validate the analyses developed and demonstrate the feasibility of the proposed converter.